Capacity assesment of street and road network in traffic control systems - Озтюркер, Марина Сергіївна (Eastern-European Journal of Enterprise Technologies, 2013)
Promising way of traffic control is the introduction of automated traffic control systems, the effectiveness of which depends on the traffic model adequacy. The possibility and correctness of using the classical gas dynamics device (gas-dynamic analogy) for the townplanning capacity assessment of the main street and road network was examined. The method of the town-planning capacity assessment of the main street and road network was developed on the basis of the gassupply network coordination method and taking into account the functioning features of the transport-planning systems of cities. The method allows assessing the current state of the transport-planning system and further effect of the measures on its regulation. It does not depend on the size of the city and allows considering the settlement and its influence zone as a unit